PLATELET COUNT TO SPLEEN DIAMETER RATIO AS A PREDICTOR OF ESOPHAGEAL VARICES IN PATIENTS OF LIVER CIRRHOSIS DUE TO HEPATITIS C VIRUS - Khalid Amin; Dilshad Muhammad (Journal of University Medical & Dental College, 2012)
ABSTRACT Objective: This study was carried out to find diagnostic accuracy of platelet count to spleen diameter ratio as a predictor of esophageal varices in patients of liver cirrhosis due to Hepatitis C virus taking upper gastrointestinal tract endoscopy as gold standard. Design: Cross-sectional study. Setting: DHQ Hospital, Faisalabad. Duration of study: Six (6) months from staring from April 01, 2009 to September 30, 2009. Subjects and methods: 95 patients of either sex having cirrhosis of liver secondary to Hepatitis C virus (diagnosed by coarse echo texture with reduced liver span on abdominal ultrasonography and positive polymerase chain reaction for Hepatitis C virus were considered as cirrhotic) were included in the study. All relevant investigations were carried out including upper gastrointestinal tract endoscopy, abdominal ultrasound scan, complete blood count, serum albumin level, serum billirubin level, prothrombin time (PT) and other clinical sign were recorded. Results: Forty seven (49.5%) patients were male and 48 (50.5%) patients were females. Mean platelet count was 133.22+22.83×103/mm3 of patients who have not developed varices yet and mean platelet count was 97.29+13.47×103/mm3 of patients who developed varices. Patients with varices had mean spleen diameter of 13.941±1.33 (centimeters) cms and without varices had 11.70±1.23 cms mean spleen diameter. The mean platelet count to spleen diameter ratio of patients without varices was 1162.41±242.43 and that of with varices was 704.28±142.11. Conclusion: Platelet count to spleen diameter ratio (considering >909 as normal) has good diagnostic accuracy in identifying cases with esophageal varices.